Revisiting the Entrepreneurial Commercialization of Academic Science: Evidence from “Twin” Discoveries - Marx, Matt; Hsu, David H. (Management Science, 2022)
Which factors shape the commercialization of academic scientific discoveries via startup formation? Prior literature has identified several contributing factors but does not address the fundamental problem that the commercial potential of a nascent discovery is generally unobserved, which potentially confounds inference. We construct a sample of approximately 20,000 “twin” scientific articles, which allows us to hold constant differences in the nature of the advance and more precisely examine characteristics that predict startup commercialization. In this framework, several commonly accepted factors appear not to influence commercialization. However, we find that teams of academic scientists whose former collaborators include “star” serial entrepreneurs are much more likely to commercialize their own discoveries via startups, as are more interdisciplinary teams of scientists. This paper was accepted by Sridhar Tayur, entrepreneurship and innovation.